HUBUNGAN DURASI DAN KUALITAS TIDUR SERTA KONSUMSI SERAT DENGAN KADAR GLUKOSA DARAH PADA PENDERITA DIABETES MELLITUS TIPE 2 DI PUSKESMAS KUTABUMI KABUPATEN TANGERANG TAHUN 2020 - Yulia Srirezeki (2020)
Type 2 diabetes mellitus is diabetes that attacks adults in 90-95% of all cases of diabetes. Diabetes mellitus is a disease that can't be cured but can be controlled by the patient's blood glucose. Risk factors that can worse glycemic control include sleep duration and quality to fiber consumption. This study aims to determine the correlation of sleep duration and quality along fiber consumption on type 2 diabetes mellitus patients in Puskesmas Kutabumi Kabupaten Tangerang 2020. This study use a cross sectional design and sample 40 patients. The data used are primary data from the PSQI and SQ-FFQ questionnaire and secondary data on blood glucose levels from the patient's medical record. Analysis of variable correlation using the spearman correlation. Analysis show there is no significant correlation between sleep duration with blood glucose levels (r=-0.2885 ; p=0.075) but variable of sleep quality and fiber consumption show a significant correlation (r=0.418,p=0.007 ; r=-0.978, p=0.000) with blood glucose levels on type 2 diabetes mellitus patients in Puskesmas Kutabumi, respectively. It can be concluded that the variable of sleep quality and fiber consumption are significantly related to patients's blood glucose level except the sleep duration variable.